PERANCANGAN UI/UX APLIKASI E-LEARNING PADA MTSS IRSYADUL ATHFAL MENGGUNAKAN METODE DESIGN THINKING - Sunaryana, Sunaryana; Nisa, Khoirun (JURNAL ILMIAH INFORMATIKA, 2024)
MTsS Irsyadul Athfal is a secondary school after graduating from elementary school, a school that applies a religious curriculum to its students. Researchers found the problem of schools that already have a website but it is not used enough to support the learning process, the website is only a promotional medium. This research aims to provide recommendations as reference material in the form of UI/UX design for E-learning applications in the form of website prototypes so that they can be developed in the future. In this research, the author uses the Design Thinking method approach to produce UI/UX designs for E-learning applications that suit user needs. There are several processes in the research method, namely empathize, define, ideate, prototype, and testing. The UI/UX design stages of E-learning applications go through several stages, namely understanding a user needs problem, needs analysis, solution analysis, making a prototype and then testing it on several users. The results of the prototype that had been designed were tested on 9 respondents using the System Usability Scale (SUS) testing method. Based on the tests that have been carried out, test results were obtained with a total SUS score value of 83.33 or (Grade Scale B).